Peran Bhabinkamtibmas Dalam Mencegah Tindak Pidana Curanmor R2 Melalui Program Jabursilan Di Polsek Jatinangor - Rendy Kurniawan Basuki (Indonesian Journal of Police Studies, 2017)
The theft of two-wheeled motor vehicles occurred in the Sumedang district community, especially in Jatinangor District, with the number of criminal acts reaching the first rank of other crimes in the past 3 years. Bhabinkamtibmas Jatinangor Sector Police have a main role preventing the criminal act. The purpose of this study includes, describing the general picture of criminal acts of 2-wheeled vehicles in Jatinangor sub-district, knowing the factors that influence it and analyzing Jabursilan program from Bhabinkamtibmas to prevent the act of crime. This research uses a qualitative approach and is carried out in Sumedang District, especially the Jatinangor Police Station. The research shows an overview of the area of Jatinangor Subdistrict, Jatinangor Sector Police and criminal acts of theft of 2-wheeled motor vehicles that occurred in Jatinangor Sector Police using ecological theory and the concept of motor vehicle theft. The implementation of the prevention of criminal activities for 2-wheeled vehicle in Jatinangor Police Station, Bhabinkamtibmas has a road-side overtime (jabursilan) program carried out by Bhabinkamtibmas, but certainly in a program there must be factors that support and inhibitors, from internal and external police.